Identifying causal relationships in strategy maps using ANP and DEMATEL. (April 2018) - Quezada, Luis E.; López-Ospina, Héctor A.; Palominos, Pedro I.; Oddershede, Astrid M.
Highlights: Identification of the causal relationships in a strategy map is proposed. The Analytic Network Process (ANP) is used to create an Initial Influence Matrix. DEMATEL is used to obtain the relationships between strategic objectives. The proposed method is applied in a manufacturing company. Abstract: This paper presents a method for identifying the causal relationships between strategic objectives in a strategy map of a Balanced Scorecard. The Analytic Network Process (ANP) is used to estimate the direct influence between strategic objectives, and the Decision Making Trial and Evaluation Laboratory (DEMATEL) is used to obtain a matrix containing the full influences (direct and indirect) between those factors. Finally, a criterion is used to select those relationships that are important enough to be considered in the Impact-relation map defined by DEMATEL. The literature shows some cases in which ANP and DEMATEL are combined to build a strategy map; however, they are used in a completely different way from how they are utilized in the method proposed in this paper. As an illustration, the method is applied in a manufacturing company.